(untitled) (Bioscience Journal, 2023)
To analyze the efficacy and psychometric properties of the Knowledge, Attitudes, and Practices Questionnaire when applied to adolescents. It was a cross-sectional construct validation study. Ten questions on the knowledge of HIV/AIDS were selected from the questionnaire for further data analysis and applied to 623 adolescents attending high school. The Statistical Package for the Social Sciences (SPSS) 25.0™ and Stata 14.0 software processed the data. Cronbach’s Alpha verified the reliability of items, and the mean of each value ranged from 0.198 to 0.379. Factor analysis assessed the structure of correlations between variables. The resulting factors were lifestyle/habits, preventive actions, and endogenous and exogenous transmission. The scale was reliable for the studied population, ensuring the quality of the instrument.